2022
DOI: 10.3390/jcm11102752
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Laryngeal Endoscopy: Systematic Review and Meta-Analysis

Abstract: Background: Early diagnosis of laryngeal lesions is necessary to begin treatment of patients as soon as possible to preserve optimal organ functions. Imaging examinations are often aided by artificial intelligence (AI) to improve quality and facilitate appropriate diagnosis. The aim of this study is to investigate diagnostic utility of AI in laryngeal endoscopy. Methods: Five databases were searched for studies implementing artificial intelligence (AI) enhanced models assessing images of laryngeal lesions take… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 39 publications
0
15
0
3
Order By: Relevance
“…For extramedullary plasmacytomas, ESMO guidelines recommend either whole-body magnetic resonance imaging (MRI) or a positron emission tomography/computed tomography (PET/CT) ([ 155 ]. Although not supported by the guidelines, it seems reasonable to additionally incorporate image-enhanced endoscopy techniques in cases of a suspected laryngeal involvement, which are widely used in other laryngeal disorders [ 156 , 157 ].…”
Section: Discussionmentioning
confidence: 99%
“…For extramedullary plasmacytomas, ESMO guidelines recommend either whole-body magnetic resonance imaging (MRI) or a positron emission tomography/computed tomography (PET/CT) ([ 155 ]. Although not supported by the guidelines, it seems reasonable to additionally incorporate image-enhanced endoscopy techniques in cases of a suspected laryngeal involvement, which are widely used in other laryngeal disorders [ 156 , 157 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some other types of endoscopic images-based deep learning applications include (a) detection of nasopharyngeal malignancies 73 , and segmentation of granulomas and ulcerations on images acquired by laryngoscopy 74 , (b) an end-to-end deep learning algorithm to segment and measure laryngeal nerves during thyroidectomy (a surgical procedure) 75 , and (c) deep-learning-based anatomical interpretation of video bronchoscopy images 76 . A recent review and meta-analysis paper on laryngeal endoscopy 77 suggested the AI models presented high overall accuracy between 0.806 and 0.997. However, this review did not show details on any AI model and used sample sizes.…”
Section: Methodsmentioning
confidence: 99%
“…Die laryngeale Endoskopie liefert eine große Menge an diagnostisch wertvollem Bildmaterial. Unterstützende Methoden wie die Erkennung von organisch veränderten Schleimhäuten, sowie analysierende Verfahren [8] wie die Bestimmung des zeitlichen Schwingungsverhalten der Stimmlippen sind KI-Ansätze, die sich in der laryngealen Endoskopie etabliert haben [9]. Ein zusätzliches Anwendungsgebiet kann die Auswertung von Schluckprozessen sein, indem KI-Systeme die Muskelbewegungen im Kehlkopf und Rachen analysieren und dadurch Anomalien erkennen können.…”
Section: Künstliche Intelligenz In Der Laryngealen Endoskopieunclassified
“…Eine kürzlich veröffentlichte Studie hat sich damit beschäftigt, inwieweit KI-Methoden, insbesondere tiefe neuronale Netze, in der Lage sind laryngeale Läsionen zu identifizieren [8]. Die Autoren konnten durch die Analyse von 11 Veröffentlichungen zeigten, dass KI-Algorithmen sowohl im Weißlicht als auch im NBI-Modus eine hohe Spezifität von 95 % aufweisen.…”
Section: Anomalien Erkennenunclassified
See 1 more Smart Citation